Genome-Wide Association Analysis and Genomic Prediction for Adult-Plant Resistance to Septoria Tritici Blotch and Powdery Mildew in Winter Wheat - Alemu, Admas; Brazauskas, Gintaras; Gaikpa, David S.; Henriksson, Tina; Islamov, Bulat; Jørgensen, Lise Nistrup; Koppel, Mati; Koppel, Reine; Liatukas, Žilvinas; Svensson, Jan T.; Chawade, Aakash (Frontiers in Genetics, 2021)
Septoria tritici blotch (STB) caused by the fungal pathogen Zymoseptoria tritici and powdery mildew (PM) caused by Blumeria graminis f.sp tritici (Bgt) are among the forefront foliar diseases of wheat that lead to a significant loss of grain yield and quality. Resistance breeding aimed at developing varieties with inherent resistance to STB and PM diseases has been the most sustainable and environmentally friendly approach. In this study, 175 winter wheat landraces and historical cultivars originated from the Nordic region were evaluated for adult-plants resistance to STB and PM in Denmark, Estonia, Lithuania and Sweden. Genome-wide association study and genomic prediction were performed based on the adult-plants response to STB and PM in field conditions using 7,401 SNP markers generated by 20K SNP chip. Genotype-by-environment interaction was significant for both disease scores. GWAS detected stable and environment-specific QTLs on chromosomes 1A, 1B, 1D, 2B, 3B, 4A, 5A, 6A and 6B for STB and 2A, 2D, 3A, 4B, 5A, 6B, 7A and 7B for PM adult-plant disease resistance. Genomic prediction accuracy was improved when assisted with QTL from GWAS as a fixed effect. The GWAS-assisted GP accuracy ranged within 0.53 – 0.75 and 0.36 – 0.83 for STB and PM, respectively, across the tested environments. This study highlights that landraces and historical cultivars are a valuable source of adult-plant resistance to STB and PM. Such germplasm could be used to identify and introgress novel resistance genes to modern breeding lines.